1976
DOI: 10.1080/03079457608418198
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma synoviaein the guinea‐fowl

Abstract: A mycoplasma strain, isolated from natural synovitis of guinea-fowl, was identified as Mycoplasma synoviae. In experimental infection this agent showed clear pathogenicity for guinea-fowl, and to a lesser degree for chickens. In guinea-fowl the strain was more likely to result in synovitis and amyloidosis when inoculated by the intravenous route and to produce sinusitis after intrasinusal inoculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Route of 50% intranasal-conjunctivalj 50% intraperitoneal intranasal-conjunctival administration It has been shown that the guinea-fowl is susceptible to all common and well-known viral diseases of gallinaceous birds (among others, Tanyi, 1974;Lage et al, 1974;Pascucci et al, 1976;Nedyalkov, 1977;Nedyalkov et al, 1979;Yakimov et al, 1979;Geneste, 1981;Gough & Spackman, 1981;Ibragimov & Trubitsin, 1989;Misciattelli et al, 1981;Misciatelli et al, 1982;Pascucci et al, 1982;Kirev et al, 1983;Kirev, 1984;Watanabe & Ohmi, 1983;Toshkov et al, 1984;Cowen et al, 1988;Kles et al, 1988;Brahem et al, 1992). Pancreatitis aetiologically attributed to adenoviruses was reported in 3 to 4-week-old guineafowl (Reece & Pass, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Route of 50% intranasal-conjunctivalj 50% intraperitoneal intranasal-conjunctival administration It has been shown that the guinea-fowl is susceptible to all common and well-known viral diseases of gallinaceous birds (among others, Tanyi, 1974;Lage et al, 1974;Pascucci et al, 1976;Nedyalkov, 1977;Nedyalkov et al, 1979;Yakimov et al, 1979;Geneste, 1981;Gough & Spackman, 1981;Ibragimov & Trubitsin, 1989;Misciattelli et al, 1981;Misciatelli et al, 1982;Pascucci et al, 1982;Kirev et al, 1983;Kirev, 1984;Watanabe & Ohmi, 1983;Toshkov et al, 1984;Cowen et al, 1988;Kles et al, 1988;Brahem et al, 1992). Pancreatitis aetiologically attributed to adenoviruses was reported in 3 to 4-week-old guineafowl (Reece & Pass, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, although the proportion of embryos with M. synoviae infection could exceed 36%, there was no correspondingly high clinical incidence in broiler chickens of Chinese native breeds. It might suggest that, in addition to the potential of chickens to produce anti- M. synoviae antibodies [28] and virulence differences between M. synoviae isolates [29–31], maternal antibodies against M. synoviae could inhibit M. synoviae activity in vivo at early ages and the developmental window when chickens were negative for the M. synoviae antibody - might play a key role in M. synoviae reproduction in hosts. Therefore, improving maternal antibody levels in developing chickens and effectively controlling M. synoviae activity during the developmental window when chickens are negative for the M. synoviae antibody might an efficient strategy to prevent M. synoviae infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot be ignored that this species could be a host of this agent. Pascucci et al (1976) reported natural sinovitis by Mycoplasma synoviae in Numida meleagris in Italy and there are researchers who consider its occurrence to be common in this poultry species (Friend & Franson 1999).…”
Section: Discussionmentioning
confidence: 99%